Transformaciones productivas e inserción comercial de los nuevos Estados Miembros: Una mirada desde España. - Álvarez, Ignacio; Luengo, Fernando (Papeles del Este, 2007)
After the difficult crisis and the adjustment process that the countries of Eastern Europe experienced immediately after the fall of the Berlin Wall, a new phase of productive and business reorganization began in the mid-1990’s. Since then, the entry of significant investments in some of these countries, the subcontracting processes of numerous European firms and the policies applied by the new reformist governments have changed the productive and commercial map of these economies. In this way, the amount, the market share and the technological range of exports from these economies have noticeably increased in terms of flows to the European Union. This evolution contrasts with the productive and commercial inertia in which the Spanish Economy has been immersed during the last decade.